City Limits Images of Boston in Transition - Wise, Kelly (Northeastern University Press, 2019)
Photographs show family celebrations, religious rituals, the homeless, couples, children, bodybuilders, parades, street scenes, and shops in each section of Boston. Originally published by Northeastern University Press in 1987. With a new foreword by B. D. Colen.